A Low-Profile Compact Meander Line Telemetry Antenna with Low SAR for Medical Applications. (12th August 2022) - Sulaiman, N. H.; Abbasi, Muhammad Inam; Samsuri, N. A.; Rahim, M. K. A.; Seman, F. C.
Abstract : A low-profile Compact Meander Line Telemetry Antenna (CMLTA) operating at 402.5 MHz for the Medical Implant Communication System (MICS) band medical applications is introduced. The proposed antenna focuses specifically on pacemaker telemetry applications. The meander line technique with an open loop configuration and simple transmission line feeding mechanism has been used for achieving the compact design. Based on the theory of surface current distribution, the proposed technique provides the opportunity to increase the electrical dimensions while decreasing the physical dimensions of the antenna. Further design optimization is carried out to optimize the overall antenna size to a maximum volume of 4080 mm 3 . By introducing CMLTA, the size of the antenna is reduced by 79% as compared to the previous work. The proposed antenna demonstrated satisfactory performance with 10 dB bandwidth of 6.17%, a maximum gain of -22 dBi and an EIRP of -25.28 dBi. The analysis of Specific Absorption Rate under premise use of 1 W input power provided the maximum 1 g and averaged 10 g SAR of 74.7 W/kg and 17.7 W/kg, respectively, demonstrating a satisfactory level according to the IEEE standard safety guidelines. Fabrication and measurements are carried out where measured results are found to be in good agreement with the simulated results. With the optimized dimensions, satisfactory gain, EIRP, and SAR performance, the proposed CMLTA is deemed suitable for pacemaker telemetry applications for effective communication.